THE PREVALENCE OF HELICBACTER PYLORI AMONG PATIENTS COMPLAINING FROM ABDOMINAL PAIN - Ahed J. Al-Khatib; Ahmed Saber Abu-zaiton (European Scientific Journal, ESJ, 2013)
Helicobacter pylori has been associated with a number of gastrointestinal disorders including gastritis, peptic ulcer disease, gastric adenocarcinoma and gastric mucosa-associated lymphoid tissue (MALT) lymphoma. The present study was conducted to determine the prevalence of Helicobacter pylori infection among patients complaining from abdominal pain and visiting internal medicine clinics. It was also purposed to investigate the relationship between both age and sex with Helicobacter pylori infection. A retrospective study was conducted and included 101patients with abdominal pain. The results showed that the prevalence of IgG against Helicobacter pylori infection is 85%, while about 38.6% of cases were positive for IgA against Helicobacter pylori. No significant relationships were found for IgG, IgA with age and sex (p value >0.05). Taken together, the study showed high prevalence of H. pylori infection among patients complaining of abdominal pain. H.pylori infection is not associated significantly with age and sex.